Material identification by surface reflection analysis in combination with bundle adjustment technique - Orun, AB; Alkis, A (ELSEVIER, 2003)
This work aims to investigate a unified method for surface analysis and remote surface identification. The work includes two independent and simultaneously operating techniques which exploit both the local surface geometry (by bundle adjustment technique) and the microstructure of the material surface (whose image is generated by laser-surface interaction). The unification of these two techniques enables the unambiguous identification of surface type at any orientation. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: photogrammetry; CCD camera; surface texture identification; active vision; classification; Computer Science